2014
DOI: 10.1248/bpb.b13-00678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oils and Emulsifiers on the Skin Penetration of Stearyl Glycyrrhetinate in Oil-in-Water Emulsions

Abstract: We investigated whether an emulsifier or an emulsified oil affects the skin penetration of stearyl glycyrrhetinate (SG) when it is applied in an oil-in-water (O/W)-type emulsion under finite dose conditions in vitro. SG has a high molecular weight (MW: 723) and high lipophilicity (log P: 15.6). Skin penetration of SG applied with O/W emulsions was evaluated using 6 types of emulsifiers that are commonly used in cosmetics; however, no significant differences were observed between these emulsifiers. When applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…8,9) In the present study, the effect of esters on artificial membrane permeation were evaluated and the obtained relationships between physical properties and the amount of compounds that permeated were almost similar to previous results that evaluated rat, [15][16][17] porcine, 19,20) and human 18) skins. Thus, although future research on the correlation between the permeability of artificial membrane and porcine or human skin from esters will be needed, silicone and Strat-M ® membranes might be useful in the development of pharmaceutical and cosmeceutical products.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…8,9) In the present study, the effect of esters on artificial membrane permeation were evaluated and the obtained relationships between physical properties and the amount of compounds that permeated were almost similar to previous results that evaluated rat, [15][16][17] porcine, 19,20) and human 18) skins. Thus, although future research on the correlation between the permeability of artificial membrane and porcine or human skin from esters will be needed, silicone and Strat-M ® membranes might be useful in the development of pharmaceutical and cosmeceutical products.…”
Section: Discussionsupporting
confidence: 87%
“…It has also been found that ketoprofen exhibited increased permeation through hairless rat skin when it was dissolved in low MW esters, 16) and the permeability of stearyl glycyrrhetinate through Yucatan micropig skin with a finite dose was affected by the surface tension and MW of the vehicle. 19) Thus, the common properties of these permeation enhancers are their low MWs and surface tension. Similarly, in the present study, it was evident that the amounts of the model compounds that permeated through the membranes were higher when esters with low MWs and low surface tension were used as a vehicle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…oleic acid and glyceryl trioleate) disrupt the stratum corneum lipids, thus enhancing the penetration [21,22,23,24]. Leite-Silva et al [22] reported that the formulation containing paraffin oil acts as a penetration enhancer for zinc oxide nanoparticles which, along with titanium dioxide nanoparticles, normally do not penetrate through the barrier of the stratum corneum [25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%